Contact With Nature as a Mental Health Buffer for Lower Income Communities During the COVID-19 Pandemic - Pearson, Amber L.; Horton, Teresa; Pfeiffer, Karin A.; Buxton, Rachel; Gardiner, Joseph; Liu, Wei; Hunter, Ruth F.; White, Mathew P. (Frontiers in Sustainable Cities, 2021)
Despite a growing number of research outputs on the importance of nature contact during the COVID-19 pandemic, we know of no longitudinal research conducted prior to and during the pandemic among low-income and minority ethnicity populations, i.e. those that might be most affected. Furthermore, we have scant information about how and to what degree contact with nature might protect mental health or mitigate worsening of mental health during the pandemic. We filled these gaps using a subset of a longitudinal study of n = 86 individuals in low-income, predominantly African American, neighborhoods in Detroit, MI, USA. The study addressed the following research questions: 1) did self-reported use and perceived value of nature change during, versus prior to, the pandemic; 2) did perceived access to outdoor spaces buffer people against mental health issues such as stress, anxiety and depression symptoms; or 3) did objectively measured quality of nature views from home buffer people against mental health issues, taking into account relevant covariates and pandemic experiences (e.g., loss of employment, death of a friend/relative)? While attitudes to nature improved slightly from pre- to during the pandemic, we also observed significant decreases in most types of outdoor physical activity and passive enjoyment of nature (e.g., smelling plants/rain). We found a positive association between visibility of greenspace and perceived stress and anxiety, which not only contradicts previous research findings, but was especially surprising given that overall there was a decrease in perceived stress from 2019-2020. We did not detect associations between perceived access/use of nature and mental health. However, higher depressive symptoms were associated with exposure to more COVID-19-related stressors (lost employment, death of friends from COVID-19, etc.). Taken together, our results indicate that COVID-19 may serve to prolong or exacerbate mental health issues, rather than create them, in this population and that low quality greenspace may perhaps limit the ability for nature view to buffer mental health during the pandemic.